Parenthetical Clauses in the Qurʼān - Dror, Yehudit (Research in Language, 2018)
In the few traditional Arabic grammatical sources that address the term parentheticals it is usually defined as the insertion of a clause between two other clauses, or between two syntactic components, for taʼkīd “emphasis.” In this article I examine Qurʼānic parenthetical clauses in the theoretical framework of relevance theory. It transpires that the parenthetical clause is placed where it achieves optimal relevance and therfore the conveyed utterance does not require the addresses to waste any efforts trying to procees the information and correctly interpret it. Optimal relevance also means having a contextual effect. The Qur’ānic parenthetical clauses have one of the following contextual effects: They serve to affirm God’s omnipotence, indicating that only God produces suras, created heaven and earth. He is the forgiver and all depends on His will; to explain what it meant by a specific statement or to explain the reason behind a certain action; to qualify, to highlight a specific characterization, for example, one of the parenthetical clauses modify the Qur’ān as the truth from God; to provide background information, which could explain further developments in the narrative.